Three Cases of Emergency Department Medical Malpractice Involving “Consultations”: How Is Liability Legally Determined? - Alaa Aldalati; Venkatesh R. Bellamkonda; Gregory P. Moore; Alexander S. Finch (Clinical Practice and Cases in Emergency Medicine, 2021)
This article presents three successfully litigated medical malpractice cases involving emergency physicians and consultants. We discuss the respective case medical diagnoses, as well as established legal principles that determine in a court proceeding which provider will be liable. Specifically, we explain the legal principles of “patient physician relationship” and “affirmative act.”